2004
DOI: 10.1021/jp037670m
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Solvation Properties of 2-Nitrophenyloctyl Ether, Nitrobenzene, and n-Octanol as Assessed by Ion Transfer Experiments

Abstract: The lipophilicity of the anionic forms of drugs and model compounds was assessed by their transfer across (i) the water-2-nitrophenyloctyl ether (NPOE), (ii) the water-nitrobenzene (NB), and (iii) the water-noctanol interfaces by using the three-phase electrode technique. The lipophilicities, expressed in terms of logarithm of partition coefficients, range for the studied anions from -3.46 to 0.68 (log P A -,aq QNPOE ) for NPOE, from -3.81 to 2.62 (log P A -,aq QNB ) for NB, and from -6.20 to -3.20 (log P A -,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 44 publications
3
85
1
3
Order By: Relevance
“…This equation is obtained by applying equation (6) to each simulation (denoted by subscripts I and II), and combining both expressions to eliminate ξ (assuming that this value does not depend on the box size). The bulk correlation length itself can then be extracted from equation (6) using the value of γ cw calculated in equation (10).…”
Section: Interfacial Tensionmentioning
confidence: 99%
“…This equation is obtained by applying equation (6) to each simulation (denoted by subscripts I and II), and combining both expressions to eliminate ξ (assuming that this value does not depend on the box size). The bulk correlation length itself can then be extracted from equation (6) using the value of γ cw calculated in equation (10).…”
Section: Interfacial Tensionmentioning
confidence: 99%
“…3 In the past decade, 2-nitrophenyl n-octyl ether (NPOE) has emerged as a viable alternative, and it is seen as one of the most promising solvents in ion transfer studies across liquid|liquid interfaces. 2,[4][5][6][7][8][9][10][11][12] Compared to the other organic solvents, NPOE has a relatively low solubility in water, a low vapor pressure, and is not known to be highly toxic. 3 In addition, NPOE has a high molar volume and a medium permittivity ( rel ) 24.2), which makes it also a good solvent for ionic solutes.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10] It is also worth mentioning that a recent study has shown that the solvation properties of nitrobenzene and NPOE toward ionic species are very similar. 11,12 In contrast, few theoretical studies have been devoted to probe such organic solvents. NB has been studied by molecular simulation in the context of light scattering, 13 and of liquid|liquid interfaces, [14][15][16] as well as for the optimization of force-field parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Details of all the log P values for ions and ionic species are in Table 5 In addition to log P values for ions obtained from solubility or distribution experiments, there are a number of log P values from electrochemical experiments [43][44][45][46][47][48]. Unfortunately, there is no consistency between the two sets of log P values.…”
Section: Resultsmentioning
confidence: 99%